Accounting Student Ethics Based on Gender - Nurul Fauziyyah; Alviansyah Sugama (Jurnal Akuntansi)
This research aims to provide a comprehensive analysis of ethical behavior exhibited by accounting students, with a focus on gender differences. The study involved an online survey of 124 accounting students from various universities in Indonesia, both public and private. The results of data analysis using an independent t-test indicated that there were no significant differences in the ethical behavior of accounting students based on gender. The implications of this research are significant in the context of accounting and business education in Indonesia. These findings indicate gender equality in the ethical behavior of accounting students. Therefore, accounting education can maintain a balanced approach in teaching accounting ethics without overly emphasizing gender differences. Students need to continue fostering the development of ethical character throughout their studies, not only in ethics courses but also in the general curriculum. Furthermore, this research can serve as a foundation for further studies that explore other factors influencing the ethical behavior of accounting students in Indonesia. The results are expected to support gender equality in accounting practices and education in the country, creating a more ethical and professional business environment.